STRATEGI MEMBANGUN ZONA INTEGRITAS ANTI KORUPSI DI POLRES KOTA BANDARA SUKARNO HATTA - Agung Pujianto (Master of Public Administration, Universitas Slamet Riyadi, 2023)
This study aims to describe the strategy of building an anti-corruption integrity zone at the Soekarno Hatta Airport City Police to make services better. This type of research is development research through qualitative descriptive. The subjects of this study were employees at Soekarno Hatta Airport who were the main informants. Sources of data from this study are informants, documents and events. The data obtained by using purposive sampling. The data analysis method in this qualitative research is an interactive data analysis method. The results determined that the SWOT matrix analysis produced 6 alternative strategies, namely increasing the professionalism, fulfilling the infrastructure, having a budget, increasing human resources, giving regulations to prevent corruption and giving strict sanctions. This research finds the twists and turns of the Polres' efforts in implementing strategy, innovation, empowering employees as human capital and the results of building integrity and anti-corruption zones. The conclusion is that the strategy to build an anti-corruption integrity zone at the Soekarno Hatta Airport City Police has not run optimally, because there are still several members' rights that have not been fulfilled. Suggestion for the chief of the police resort (Kapolres) is that he can fulfill the rights of members of the Soekarno Hatta Airport Police. Keywords: Strategy, integrity, anti-corruption